Efficient extraction of silica from openly burned rice husk ash as adsorbent for dye removal. (20th December 2022) - Haider, Jahid Bin; Haque, Md. Irfanul; Hoque, Mozammel; Hossen, Md. Mosaddek; Mottakin, M.; Khaleque, Md. Abdul; Johir, M.A.H.; Zhou, John L.; Ahmed, Mohammad Boshir; Zargar, Masoumeh
Abstract: Rice is the staple food in many countries including Bangladesh. In Bangladesh, >80% of the total irrigated area is planted with rice, which generates a huge amount of rice husk (RH) as a solid waste which requires proper management. This study, therefore, aimed to extract amorphous silica from openly burned rice husk ash (RHA) using a simple method by avoiding calcination or combustion processes. The extracted silica was then applied for the removal of environmental contaminants i.e., methylene blue dye from an aqueous solution. It was found that the yield of silica produced from sulfuric acid-pretreated RHA was 72.4%. The FTIR absorption peaks at 1057 and 783 cm −1 indicate the presence of a highly condensed silica-containing asymmetric and symmetric siloxane (Si–O–Si) network mixture. The broad maximum bond peak intensity at 2θ = 22° by x-ray diffraction analysis also indicates that the produced silica was amorphous with a mesoporous structure. The surface area of sulfuric acid treated RHA-based silica was 183 m 2 /g. This silica resulted in a maximum adsorption capacity of 107 mg/g of methylene blue at pH 8 with a faster equilibrium reached at 60 min. The mechanistic study indicated that both Langmuir and Freundlich adsorption isotherms were both fitted well which suggested homogeneous adsorbent surfaces involving monolayer and multilayer adsorption processes. Graphical abstract: Image 1 Highlights: Silica synthesis from rice husk ash is energy efficient by avoiding calcination. Highly pure silica is produced with high BET surface area. Produced silica adsorbs considerable amount of dye from aqueous solution. Rice husk ash is used as a resource instead of waste for dumping.